The impact of CEDAW on muslims marriage and family: the Malaysian perspective - Abdul Hak, Nora (2011)
The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) is the international human rights treaty that is exclusively devoted to gender equality. It was adopted by the United Nations General Assembly on 18 September 1979 and entered into force on 3 September 1981. As of 1 March 2010, CEDAW has 186 States parties, representing almost the entire international community. It is one of the most widely accepted human rights treaties and is often described as an international bill of rights for women. The Convention which is consisted of a preamble and 30 articles defines discrimination against women and sets up an agenda for national action to end such discrimination. Article 16 of CEDAW concerns the issue of marriage and family relations. It asserts the equal rights and obligations of women and men with regard to choice of spouse, equal rights and responsibilities toward children, including the right to freely determine the number and spacing of children and the means to do so, and the same rights to property. It provides that the States Parties shall take all appropriate measures to eliminate discrimination against women in all matters relating to marriage and family relations and in particular shall ensure, on a basis of equality of men and women. Thus, the paper deliberates on the relevant articles of the Convention especially Article 16 which is included with the aim to support marriage and family institution. It also focuses on the extent of compliance and responses by the Malaysian government to Article 16 of the Convention. It is viewed that these responses must be in line with the spirit of the National Family Policy which is formulated with the aim to strengthen the family institution. The National Family Policy will be the main guideline for all parties to include the family perspective in legislation, policies, procedures, rules and development programmes. At the end, it is hoped that any compliance to CEDAW by the Government must take into consideration of the sensitivity of the Malaysian which is multi-religious, multi-racial and multi-cultural society.